Model of Coping Strategy, Social Interaction, and Self-Adjustment - Muarifah, Alif; Barida, Muya (Universitas Ahmad Dahlan, 2018)
The purpose of the present study was to examine the model between coping strategy, social interaction, and self-adjustment. The respondents of the present study were 660 17-18 years old students of junior high schools in the Special Region of Yogyakarta, both state and private school. The respondents were selected by using proportional sampling from a population of 128,288 students. The present study employed quantitative correlational research design. The data were analyzed using SEM. The result of the study showed that 1) social interaction was intervening variable (mediation) between coping strategy and self-adjustment. Coping strategy holds significant effect on social interaction, social interaction significantly affects self-adjustment, and 2) Coping strategy also possessed a direct correlation with self-adjustment. The result of the study can be used as consideration of the use of a coping strategy in improving an individual's self-adjustment.